(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Blood transfusions, dissent, faith. Therapeutic self-determination procedures as a form of protection of religious freedom The essay investigates the relevance of therapeutic selfdetermination procedures in order to protect religious freedom, where the patient’s healthcare choice is a manifestation of his religious identity. The analysis starts from a 2024 ruling by the European Court of Human Rights, which condemned the Spanish State for not having respected the therapeutic self-determination procedures established by law, without however censuring all the conducts that contributed to limiting the right to health and the right to religious freedom. These are conducts that are relevant for the purposes of quantifying the compensable damage, as appreciable in the case in which the prejudice also affects the individual religious dimension, in addition to the therapeutic self-determination of the person. SOMMARIO: 1. Identità religiosa e scelte sanitarie omissive nel diritto europeo e nella legislazione spagnola - 2. Il caso Pindo Mulla vs. Spagna: profili fattuali e decisioni giurisdizionali nazionali - 3. Il giudizio di Strasburgo, tra principi generali e violazioni particolari dell’autodeterminazione terapeutica religiosamente motivata - 4. Le lacune della pronuncia europea e i possibili profili evolutivi a tutela della libertà religiosa